Design of marine facilities for the berthing, mooring, and repair of vessels - Gaythwaite, John (American Society of Civil Engineers, 2004)
"This handbook for practicing engineers covers the design of marine structures for the berthing, mooring, and repair of vessels, including piers, wharves, bulkheads, quaywalls, dolphins, dry docks, floating docks, and various ancillary structures. Descriptions of vessel characteristics, dry dock types, and inspection, as well as assessment of existing facilities are all incorporated in this comprehensive marine facilities reference. Civil and structural engineers involved in port and harbor structures design will find this book an excellent introductory text because it covers all structural types that are likely to be encountered in port, harbor, and marine terminal designs."--BOOK JACKET.Title Summary field provided by Blackwell North America, Inc. All Rights Reserved